Dadra and Nagar Haveli Draft Annual Plan 1996-97 - Planning Commission (Planning Commission, 1996)
Dadra and Nagar Haveli is an uni-district territory. It is a predominantly a tribal area with about 80 percent tribal population. It is sandwitched between the industrially prosperous States of Gujarat and Maharashtra. The territory has been declared as industrially backward area. However, the proximity to industrially advanced towns like Bombay, Surat, Ahmedabad, Rajkot and Bhavnagar has had some spiral ever-effect Besides, the picturesque territory together with a calm and peaceful environment attract both the industrial house as well as the tourist.
Union Territory of Dadra and Nagar Haveli, Department of Planning and Statistics